Oestradiol restores cell proliferation in dentate gyrus and subventricular zone of streptozotocin-diabetic mice - Saravia, Flavia Eugenia (2004)
Type 1 diabetes mellitus correlates with several brain disturbances, including hypersensitivity to stress, cognitive impairment, increased risk of stroke and dementia. Within the central nervous system, the hippocampus is considered a special target for alterations associated with diabetes. Neurogenesis is a plastic event restricted to few adult brain areas: the subgranular zone of the dentate gyrus and the subventricular zone (SVZ). First, we studied the ability for neurogenesis in the dentate gyrus and SVZ of chronic diabetic mice induced by streptozotocin (STZ). Using bromodeoxyuridine (BrdU) labelling of cells in the S-phase, we observed a strong reduction in cell proliferation rate in both brain regions of diabetic mice killed 20 days after STZ administration. Second, because oestrogens are active neuroprotective agents, we investigated whether 17beta-oestradiol (200 micro g pellet implant in cholesterol during 10 days) restored brain cell proliferation in the diabetic mouse brain. Our results demonstrated a complete reversibility of dentate gyrus cell proliferation in oestrogen-treated diabetic mice. This plasticity change was not exclusive to the hippocampus because oestrogen treatment restored BrdU incorporation into newborn cells of the SVZ region of diabetic animals. Oestrogen treatment did not alter the hyperglycemic status of STZ-diabetic mice. Moreover, oestrogen did not modify BrdU incorporation in control animals. These data show that oestrogen treatment strongly stimulates brain neurogenesis of diabetic mice and open up new venues for understanding the potential neuroprotective role of steroid hormones in diabetic encephalopathy.